Production of human CAR-NK cells with lentiviral vectors and functional assessment in vitro - Ana L. Portillo (Elsevier, 2021)
Summary: Although natural killer (NK) cells have become a promising immune effector cell for chimeric antigen receptor (CAR)-based therapy, generating human CAR-NK cells with high transgene efficiency has been challenging. In this protocol, we describe how to generate CAR-NK cells with transduction efficiencies >15% from healthy donor ex vivo expanded NK cells using third generation lentiviral vectors (LVs). We also show how to assess CAR-NK cell anti-tumor function in vitro using a flow cytometry-based killing assay.For complete details on the use and execution of this protocol, please refer to Portillo et al. (2021).